Fibonacci Circles

Geometry Level 5

Consider two circles C 1 C_1 and C 2 C_2 tangent to each other and also to a line L L at points T 1 T_1 and T 2 T_2 .

We draw a chain of circles C 3 , C 4 , C 5 , C_3,C_4, C_5, \cdots such that C n C_n is tangent to C n 1 , C n 2 C_{n-1},C_{n-2} and the line L L .

This sequence of circles approaches a limiting point T T_\infty on the line L L .

If T T_\infty divides the segment T 1 T 2 T_1T_2 into equal parts, then find the ratio of the radius of C 1 C_1 to the radius of C 2 C_2 .

Notation: φ = 1 + 5 2 \varphi = \dfrac {1+\sqrt 5}2 denotes the golden ratio .

1 2 φ \dfrac{1}{2\varphi} φ 4 \dfrac{\varphi}{4} 1 φ + 1 \dfrac{1}{\varphi+1} φ 1 \varphi-1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 26, 2020

Let the red circle be C 1 C_1 , the blue circle be C 2 C_2 , radius of C n C_n be r n r_n , and the length T j T k = j k T_jT_k = \ell_{jk} .

Then 12 = ( r 1 + r 2 ) 2 ( r 1 r 2 ) 2 = 2 r 1 r 2 \ell_{12} = \sqrt{(r_1+r_2)^2-(r_1-r_2)^2} = 2\sqrt{r_1r_2} and 13 + 23 = 12 2 r 1 r 3 + 2 r 2 r 3 = 2 r 1 r 2 r 3 = r 1 r 2 r 1 + r 2 \ell_{13} + \ell_{23} = \ell_{12} \implies 2\sqrt{r_1r_3} + 2\sqrt{r_2r_3} = 2\sqrt{r_1r_2} \implies \sqrt {r_3} = \dfrac {\sqrt{r_1r_2}}{\sqrt{r_1}+\sqrt{r_2}} . Putting r 1 = 1 \sqrt{r_1}=1 and r 2 = x \sqrt{r_2} = x , we have:

r 3 = r 1 r 2 r 1 + r 2 = x 1 + x r 4 = r 2 r 3 r 2 + r 3 = x 2 + x r 5 = r 3 r 4 r 3 + r 4 = x 3 + 2 x By proof by induction r n = r n 2 r n 1 r n 2 r n 1 = x F n 3 + F n 4 x × x F n 2 + F n 3 x x F n 3 + F n 4 x + x F n 2 + F n 3 x where F k is the k th Fibonacci number. = x F n 1 + F n 2 x \begin{aligned} \sqrt{r_3} & = \frac {\sqrt{r_1r_2}}{\sqrt{r_1}+\sqrt{r_2}} = \frac x{1+x} \\ \sqrt{r_4} & = \frac {\sqrt{r_2r_3}}{\sqrt{r_2}+\sqrt{r_3}} = \frac x{2+x} \\ \sqrt{r_5} & = \frac {\sqrt{r_3r_4}}{\sqrt{r_3}+\sqrt{r_4}} = \frac x{3+2x} & \small \blue{\text{By proof by induction}} \\ \implies \sqrt{r_n} & = \frac {\sqrt{r_{n-2}r_{n-1}}}{\sqrt{r_{n-2}}-\sqrt{r_{n-1}}} \\ & = \frac {\frac x{F_{n-3} + F_{n-4}x} \times \frac x{F_{n-2} + F_{n-3}x}}{\frac x{F_{n-3} + F_{n-4}x} + \frac x{F_{n-2} + F_{n-3}x}} & \small \blue{\text{where }F_k \text{ is the }k\text{th Fibonacci number.}} \\ & = \frac x{F_{n-1} + F_{n-2}x} \end{aligned}

Let the distance of T n T_n from T 1 T_1 be d n d_n and to simplify, n = n , n + 1 \ell_n = \ell_{n, n+1} , then

d 1 = 1 = 2 r 1 r 2 = 2 x d 2 = 1 2 = 2 x ( 1 x 1 + x ) = 2 x 1 + x d 3 = 1 2 + 3 = 2 x 1 + x ( 1 + x 2 + x ) = 4 x 2 + x d 4 = 2 x 2 + x ( 2 x 3 + 2 x ) = 6 x 3 + 2 x d 5 = 2 x 3 + 2 x ( 3 + x 5 + 3 x ) = 10 x 5 + 3 x By induction d n = 2 F n 1 x F n 1 + F n 2 x \begin{aligned} d_1 & = \ell_1 = 2\sqrt{r_1r_2} = 2x \\ d_2 & = \ell_1 - \ell_2 = 2x \left(1- \frac x{1+x}\right) = \frac {2x}{1+x} \\ d_3 & = \ell_1 - \ell_2 + \ell_3 = \frac {2x}{1+x} \left(1 + \frac x{2+x} \right) = \frac {4x}{2+x} \\ d_4 & = \frac {2x}{2+x} \left(2-\frac x{3+2x} \right) = \frac {6x}{3+2x} \\ d_5 & = \frac {2x}{3+2x} \left(3+\frac x{5+3x} \right) = \frac {10x}{5+3x} & \small \blue{\text{By induction}} \\ \implies d_n & = \frac {2F_{n-1}x}{F_{n-1}+F_{n-2}x} \end{aligned}

Since d = 1 2 = x d_\infty = \dfrac {\ell_1}2 = x ,

x = lim n 2 F n 1 x F n 1 + F n 2 x Divide up and down by F n 2 = lim n 2 x × F n 1 F n 2 F n 1 F n 2 + x Note that lim n F n + 1 F n = φ , the golden ratio = 2 φ x φ + x φ x + x 2 = 2 φ x x = φ \begin{aligned} x & = \lim_{n \to \infty} \frac {2F_{n-1}x}{F_{n-1}+F_{n-2}x} & \small \blue{\text{Divide up and down by }F_{n-2}} \\ & = \lim_{n \to \infty} \frac {2x\times \frac {F_{n-1}}{F_{n-2}}}{\frac {F_{n-1}}{F_{n-2}} + x} & \small \blue{\text{Note that }\lim_{n \to \infty} \frac {F_{n+1}}{F_n} = \varphi \text{, the golden ratio}} \\ & = \frac {2\varphi x}{\varphi + x} \\ \varphi x + x^2 & = 2\varphi x \\ \implies x & = \varphi \end{aligned}

Note that x = r 2 r 1 x = \sqrt{\dfrac {r_2}{r_1}} , therefore r 1 r 2 = 1 x 2 = 1 φ 2 = 1 φ + 1 \dfrac {r_1}{r_2} = \dfrac 1{x^2} = \dfrac 1{\varphi^2} = \boxed{\frac 1{\varphi + 1}} .

@Digvijay Singh , I finally got it.

Chew-Seong Cheong - 1 year, 2 months ago
Michael Mendrin
Mar 18, 2020

Let radii of C 1 , C 2 C_1, C_2 be r 1 , r 2 r_1, r_2 . Then

φ 2 = r 2 r 1 = φ + 1 \varphi ^2 = \dfrac{r_2}{r_1} = \varphi + 1

How did you arrive at this?

Digvijay Singh - 1 year, 2 months ago

When I get the time.

Michael Mendrin - 1 year, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...